Econometric modeling of panel data on the saving patterns of Philippine agricultural households - Alberto, Angelo M. (Philippine Statistician, 2012)
This study aims to identify significant determinants of Philippine agricultural household saving using aggregate (regional) household panel data from the Family Income and Expenditure Survey (FIES) (1991 to 2006). Two definitions of saving are used - with and without expenses on durable goods as expenditure item. Using fixed effects models for panel data, the study identifies age of household head, self-employment of household head, determinants of agricultural household saving. Self-employment, however, is significant only when expenses on durable goods is considered as an expenditure item. Also, time and cross-section fixed effects suggest that there are certain years and regions which had less agricultural household saving.